Bisphosphonates for advanced prostate cancer - Macherey, Sascha; Jordan, Karin (The Cochrane database of systematic reviews, 2017)
enesThe prevalence and incidence of pain and skeletal complications of metastatic bone disease such as pathologic fractures, spinal cord compression and hypercalcemia is high and an important contributor...enmsesdeBisphosphonates for advanced prostate cancerReview questionThis review and analysis compared the chance of pain reduction, number of bone complications (skeletal‐related events), number of deaths,...
Gesehen am 20.07.2018